FROM TRADITIONAL TO INTELLIGENT LEARNING: DEVELOPMENT OF AI-BASED MATHEMATICS LEARNING MEDIA TO STRENGTHEN DIGITAL LITERACY WITHIN A DEEP LEARNING INSTRUCTIONAL DESIGN FRAMEWORK - Silwana, Amalia; Aditya Khoirun Nisa', Lita; Widayanti, Evi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
IT-based mathematics learning media integrated with AI hold substantial potential in education. However, such media have not been widely implemented in Indonesian schools, particularly at the elementary level. In fact, one of the supporting aspects of the deep learning approach is the use of digital technology, which is closely related to digital literacy as a key 21st-century competency that students must acquire. This study aims to develop interactive mathematics learning media using GeoGebra integrated with AI (ChatGPT) to enhance students’ digital literacy and support AI-based deep learning in mathematics, specifically on the topic of the elements and nets of cube and cuboid for grade V elementary students. ChatGPT is use alongside GeoGebra in helping students understand the concepts: GeoGebra facilitated visualization and interactive simulation, while ChatGPT supports conceptual exploration and reflection. This research is a Research and Development (R&D) design using the ADDIE development model. The study was conducted at SD Muhammadiyah 15 Surabaya. The results indicate that the developed media are highly valid, with a validity score of 3.95, and highly practical, with a practicality score of 3.38. In line with the deep learning approach principles: students were able to discover the concepts of elements and nets of cube and cuboid independently and enjoyably through the integration of GeoGebra and ChatGPT (joyful learning). Consequently, the knowledge acquired by the students became meaningful (meaningful learning) and they were able to realize the learning objectives because they were deeply engaged in the process of conceptual discovery (mindful learning).